Improper Maintenance Activities Alter Benefits of Urban Stormwater Treatment in a Temperate Constructed Wetland in NSW, Australia - Wright, Aaron S.; Doblin, Martina A.; Scanes, Peter R. (Frontiers in Environmental Chemistry, 2022)
Constructed wetlands (CWs) are an effective means to treat nutrient and sediment pollution in urban stormwater runoff to minimise impact on receiving waterways. Maintenance of devices is recognised as a major contributing factor to performance. There is a lack of evidence-based guidance on maintenance activities to optimise treatment, due to a paucity of data from long-term field studies into CW performance before and after maintenance. In this study, the nutrient and sediment removal efficiency (% RE) of a CW was evaluated by calculating removal efficiencies of nitrogen (N), phosphorus (P) and total suspended sediment (TSS) following a long-term sampling program under baseflow and event flow conditions. Sampling was carried out before, during and after maintenance. Maintenance involved removing all aquatic vegetation and 200-300 mm of sediments over a 3-week period, aiming to improve the wetland’s performance. Assessment of dissolved and particulate nutrient fractions allowed a comprehensive investigation into drivers of nutrient removal efficiency. Under baseflow conditions differences in inflow and outflow pollutant concentrations were used to calculate removal efficiency and pollutant loads were used during event flow conditions. Before maintenance, during baseflow conditions the wetland was removing total N (36% RE) but exporting total P (-52% RE) and total sediment (-94% RE). During event-flow conditions all target pollutants were being removed (total N 63% RE, total P 25% RE and TSS 69% RE). During maintenance, the device continued to remove total N (18% RE) but the physical disturbance of the maintenance resulted in mass export of total P (-120% RE) and total sediment (-2,000% RE) over a short time period, effectively undoing previous treatment. After maintenance, during baseflow conditions, the wetlands' ability to treat total N decreased (28% RE), improved for total P (1% RE), and became a chronic source of suspended sediment (-127% RE). During event flow conditions, total N was no longer being treated (-19%) but total P and total suspended sediment were being retained (74%, 80% RE respectively). This study showed that the physical disturbance resulting from large-scale maintenance activities can potentially reverse years’ worth of treatment if not adequately planned and carried out with suitable controls.